Pengembangan Media Flipbook Berbantuan Augmented Reality Pada Materi IPAS Sistem Pernapasan Manusia Di Kelas V Sekolah Dasar. - Ilma Yang Fauni; Barokah Isdaryanti (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop media Flipbook assisted by Augmented Reality on human respiratory system subject of IPAS in grade V Elementary School. The method used in this research is through qualitative approaches and quantitative or R&D with the ADDIE model consisting of analyze, design, development, implementation, and evaluation. The population in the study were fifth grade students of Sibebek Elementary School. The total number of 30 students and 1 teacher. The results of the feasibility of Flipbook assisted by Augmented Reality media get 91% and 93% from material and media experts. While from teachers and students of 85% and 96.15%. Sig value. Pretest 0.200> 0.05 and posttest 0.146> 0.05 so that the data is normally. distributed. The increase in the average value (N-Gain) was 0.71 with a high category. So that the Flipbook media assisted by Augmented Reality on the material of the human respiratory system in class V are feasible and effective in improving the results in learning science on the material of the human respiratory system in grade V.